THE SOCIAL AND EDUCATIONAL SIGNIFICANCE OF APHORISMS: AN ANALYTICAL APPROACH - Jo’raqulova Hurmatoy (TADQIQOTLAR, 2025)
Annotation: This article examines the social and educational significance of aphorisms. By analyzing 50 well-known aphorisms and surveying students, the study reveals that aphorisms play a crucial role in shaping moral values, promoting civic awareness, and encouraging personal development. The findings suggest that aphorisms are effective tools in education, fostering reflective thinking and ethical understanding among young people.